ALTERNATIF MODEL STRATEGI PENGUATAN KAPASITAS KEBERDAYAAN KELEMBAGAAN KELOMPOK TANI HUTAN RAKYAT LAHAN KERING DI KABUPATEN SITUBONDO - Hartadi, Rudi; Supriono, Agus; Hariyono, Kacung; Kosasih, Safari (Jurnal Sosial Ekonomi Pertanian, 2012)
Kabupaten Situbondo is one of Kabupaten in East Java province that frequently developes dry land of community forest, particularly on the community forest-propietary. Model of policy being applied is through reinforcement of community forest farmergroup empowerement. However, there are still many obstacles for the implementation in the real field. This research is aimed to obtain alternative of strategies to solve the problem. The studied items are: (a) what internal and external key factors that cover institutional sphere on farmer group are, and (b) how the alternative strategy formulation can be viewed as effective and efficient (grand strategy) in order to reinforce in sustainably on the empowerment level of farmer group. The approach of analysis being used is matrix analysis of internal and external factors as well as grand strategy of SWOT interaction. Based on the research result, it can be found out that there are 9 factors of internal strengths, 9 factors of internal weaknesses, 7 factors of external opportunity, and there are 4 factors of external threat that cover institutional sphere of those farmer groups. Generally, condition of farmer group institutional is under strong position in the internal, and it can be more effective by utilizing potential of opportunity as well as minimizing the negative effect of existing external threats potential. The Grand strategy for reinforcing the farmer group empowerement in sustainably is by SO strategy. It means that the the superiority potential, namely internal factors should be well-managed so that this can be utilized as strength impeller (trigger/move of rule) in order to obtain the opportunities as well as minimizing negative effect of existing external threat protentials. Key Words: Â community forest, dry land, group empowerement, SWOT interaction